2011
DOI: 10.1080/00405000.2010.482341
|View full text |Cite
|
Sign up to set email alerts
|

Study of fiber packing density of lyocell ring‐spun yarns

Abstract: The study of yarn structure and related yarn properties has been the subject of much research. However, the study of the fiber packing density, which has practical significance for a number of yarns and their characteristics, has been limited to circular yarns because of the disordered yarn structure. In this paper, the fiber packing density of lyocell ring-spun yarns is determined with the image analysis method. This method does not have any limitation with regard to the fiber cross-sectional shape. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
5
1
1
Order By: Relevance
“…It is observed from our results that maximum packing density of these yarns occurs at some different distances from the yarn axis and it sharply decreases from that point towards yarn surface. Similar trends were also observed by other researchers [7,8,17,18,19]. Soni [20] and Kumar et al [21] observed maximum helix twist at some distance from the yarn axis.…”
Section: Radial Packing Density Of Control and Engineered Yarnssupporting
confidence: 91%
“…It is observed from our results that maximum packing density of these yarns occurs at some different distances from the yarn axis and it sharply decreases from that point towards yarn surface. Similar trends were also observed by other researchers [7,8,17,18,19]. Soni [20] and Kumar et al [21] observed maximum helix twist at some distance from the yarn axis.…”
Section: Radial Packing Density Of Control and Engineered Yarnssupporting
confidence: 91%
“…The calculated packing densities of the given yarns (although need more samples for verification) are comparable to the results calculated using traditional methods for yarns of similar counts. 11,22,23 This agreement, however, contradicts our expectations of getting packing density values higher than the values obtained from traditional methods that add extra porosity to the yarn structure by considering a circular cross-sectional shape of the yarn. It can be explained, on the other hand, by the decreased area of fibers detected by the automated CV segmentation method that does not consider the wall of the fiber (e.g.…”
Section: Other Yarn Case Studiescontrasting
confidence: 78%
“…Apparently, η3 is positively related with α and η2. From the previous research [3537], η2 relevant to the twist of yarn and the morphologies of single fiber and its trajectory within yarn ranges from 30% to 70% while the theoretical value of α is nearly 1%. Thus,where ηitalicair is the maximum volume fraction of air within yarn.…”
Section: Resultsmentioning
confidence: 84%